Peningkatan Respons Imun Non Spesifik Ikan Gurame Pascapemberian Ekstrak Air Panas Mikroalga Spirulina platensis (ENHANCEMENT OF NON-SPECIFIC IMMUNE RESPONSE OF OSPHRONEMUS GOURAMY AFTER GIVING OF HOT WATER EXTRACT SPIRULINA PLATENSIS) - Satyantini, Woro Hastuti; Agustono, Agustono; Arimbi, Arimbi; Sabdoningrum, Emy Koestanti; Budi, Myrna; Asmi, Lina Wafia (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Hot water extract of Spirulina platensis which is contain of lipopolysaccharide can be used as animmunostimulant. This study aimed to determine the effect of hot water extract of S. platensis throughinjection on the non-specific immune response of Osphronemusgouramy. The treatment was given throughintraperitoneal injection of hot water extract of S. platensis with doses of 1%, 10%, 20% and PBS, PhosphateBuffer Saline (control) 0.1 ml/fish. Fish reared in the aquarium (67 l volune) with density 12 fishes/aquarium with average weight of 7.5 – 8.5 g/fish. Blood samples of fish taken from the caudal vein on day0 (before administration of the extract), 3 and 5 days after administration of the extract for the measurementof total leucocytes, differential leucocytes and phagocytic activity. Results showed an increased in totalleucocytes, phagocytic activity, monocytes and neutrophils of fish that given hot water extract of S. platensis.The addition of hot water extract of S. platensis at 1% through injection gave total leucocytes, phagocyticactivity, monocytes and neutrophils on days 3 were 543.73 x 103sel/mm3,69.30%, 34.33% and 14%respectively higher and significantly different to control.
Keywords: Osphronemusgouramy; hot water extract; Spirulina platensis; non-specific immune response